A Walk on the Wild Side: The Impact of Music on Risk-Taking Likelihood - Enström, Rickard; Schmaltz, Rodney (Frontiers in Psychology, 2017)
From a marketing perspective, there has been substantial interest in on the role of risk-perception on consumer behaviour. Specific ‘problem music’ like rap and heavy metal has long been associated with delinquent behaviour, including violence, drug use, and promiscuous sex. Although individuals’ risk preferences have been investigated across a range of decision-making situations, there has been little empirical work demonstrating the direct role music may have on the likelihood of engaging in risky activities. In the exploratory study reported here, we assessed the impact of listening to different styles of music while assessing risk-taking likelihood through a psychometric scale. Risk-taking likelihood was measured across ethical, financial, health and safety, recreational and social domains. Through the means of a canonical correlation analysis, the multivariate relationship between different music styles and individual risk-taking likelihood across the different domains is discussed. Our results indicate that listening to different types of music does influence risk-taking likelihood, though not in areas of health and safety.